A clinicopathological study of severe non-haemolytic anemia in age group of 0-18 years - Dr. Rasadhar Deka; Dr. Prabir Hazarika (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Anaemia is typically defined as reduction in the haemoglobin concentration below certain value.The normal reference value of haemoglobin concentration defined by W.H.O. is 12.5gm/dl for men and women. Evaluation of the causes of severe non haemolytic anaemia seems to be important as the various causes would respond to different treatment modalities. Methods: This was a hospital based prospective study that was carried out in a tertiary referral centre for one year, from January to December 2014. A total of fifty cases were subjected for thorough clinical examination and various investigations in order to provide information to evaluate their causes. Results: The maximum numbers of cases were reported in the age group of 3-6 years with male predominance. The maximum number of cases were diagnosed as Iron Deficiency Anaemia (22%); followed by Acute Lymphoblastic Leukaemia (20%), Acute Myeloblastic Leukaemia (16%), Megaloblatic Anemia (16%), Aplastic Anemia (10%), Anemia of Chronic Disease (8%). Conclusion: Evaluation of the causes of non haemolyticanemia seems to be important because different causes would respond to different treatment modalities; thus enabling the physician to plan out a successful therapeutic outline.